The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ejogrb.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The change of fetal heart rate short-term variability during the course of histological chorioamnionitis in fetal sheep

Abstract: Our study suggests that STV increased as the fetal condition deteriorated during the course of histological CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…These results are biologically plausible because our previous animal study with an intrauterine in ammation pregnant sheep model proved that the histological in ammation directly caused metabolic acidosis, and not respiratory acidosis. 21 Previously, we have reported that labor UC and immature gestational age at delivery were related to hCAM in SPTB cases. 10 The reason why UC leads to intrauterine in ammation is still unclear.…”
Section: Discussionmentioning
confidence: 90%
“…These results are biologically plausible because our previous animal study with an intrauterine in ammation pregnant sheep model proved that the histological in ammation directly caused metabolic acidosis, and not respiratory acidosis. 21 Previously, we have reported that labor UC and immature gestational age at delivery were related to hCAM in SPTB cases. 10 The reason why UC leads to intrauterine in ammation is still unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Fetal response to mild hypoxia is initially protective. In addition, fetal response to moderate hypoxia involves substantial compensations via the autonomic (parasympathetic [vagus] and sympathetic [beta-adrenergic]) nervous system 20 - 23) . However, these compensatory mechanisms break down in the presence of severe asphyxia, and fetal brain damage can occur because central blood flow is not sufficiently maintained 24) .…”
Section: Discussionmentioning
confidence: 99%
“…This could result in underestimation of the actual fetal condition, causing a delay in the management of the abnormal FHR pattern during labor [37]. Kyozuka et al [38] reported that development of severe acidosis in a fetus because of lipopolysaccharide induced intrauterine inflammation with an impaired FHR pattern indicates low oxygenation. Therefore, a scenario in which a high DII during pregnancy can increase the risk of fetal acidosis at birth is when the intrapartum FHR pattern is modified because of severe intrauterine inflammation with resultant delay in obstetric intervention on the basis of the FHR pattern.…”
Section: Discussionmentioning
confidence: 99%